Indirect Sinus Lift Procedure with Immediate Implant Placement: A Case Report - Mody, Eesha (Indonesian Journal of Prosthodontic, 2021)
Chief Complaint: Patient complains of missing teeth in the upper left back region of the jaw Patient’s oral status: Missing teeth : 25, 26, 27, 37, fixed prosthesis: 18, 17, 16, 15, 14, 13, 12, 34, 35, implant retained prosthesis: 37, 36, 35, Siebert’s classification: Class II (Loss of ridge height with normal ridge width). Treatment plan: Implant retained prosthesis with 25,26,27 (maxillary left second premolar and molars) with indirect sinus lift surgery. Details of therapy: On CBCT examination obtained and the bone height in the region of 27 was found to be 5mm. Therefore, an Indirect Sinus Lift procedure was planned with immediate implant placement following the Hydraulic Sinus Lift Technique. The implant size was determined as 4,5 X 8.5mm. The DioNavi Sinus Lift drill kit was used. The drilling protocol to be followed for Sinus Lift procedure. For the 27 region, tissue punch was made, and sequential drilling was followed till 3.2 X 7mm drill. 3,2 X 17mm drill was used with a 5mm stopper and 4mm stopper respectively to create an opening in the sinus floor. The nozzle was then applied to the bone cavity such that the connection is airtight. The syringe, filled with normal saline, is depressed slowly, and helps in detaching the membrane from the sinus floor. Hydroxyapatite bone graft was filled into the cavity and the implant was placed 6 months post the surgical phase, phase II was carried out and the impression was made, and prosthesis delivered. Clinical significance of therapy: To achieve adequate osseointegration, there should be good quality and quantity of bone around the osteotomy. This may be compromised in edentulous posterior maxilla in the vertical direction. Therefore, the Sinus Lift procedure is helpful in overcoming this limitation.